2004
DOI: 10.1038/sj.gt.3302345
|View full text |Cite
|
Sign up to set email alerts
|

In vivo transfection of a cis element ‘decoy’ against signal transducers and activators of the transcription 6 (STAT6) binding site ameliorates the response of contact hypersensitivity

Abstract: We herein demonstrate that STAT6 plays an important role in the induction of not only acute contact hypersensitivity (CHS), but also chronic CHS in a mouse model using STAT6-deficient (STAT6 À/À ) mice. We, therefore, determine whether synthetic double-stranded DNA with a high affinity for STAT6 can be introduced in vivo as a decoy cis element to bind the transcriptional factor and block the induction of not only acute CHS but also chronic CHS. Treatment by the transfection of STAT6 decoy oligodeoxynucleotides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…34 Topical administration of an NF-kB dODN has been successfully tested in a mouse model of atopic dermatitis 35 (in comparison with betametasone 36 ), as well as in the DTH response of the same species, 37 but the potentially adverse proapoptotic effects of blocking this transcription factor must be followed. Recently, dODN blockade of STAT3, which together with NF-kB and STAT1 is implicated in psoriasis, 7 has revealed its therapeutic potential in a genetically engineered mouse model of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…34 Topical administration of an NF-kB dODN has been successfully tested in a mouse model of atopic dermatitis 35 (in comparison with betametasone 36 ), as well as in the DTH response of the same species, 37 but the potentially adverse proapoptotic effects of blocking this transcription factor must be followed. Recently, dODN blockade of STAT3, which together with NF-kB and STAT1 is implicated in psoriasis, 7 has revealed its therapeutic potential in a genetically engineered mouse model of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated therapeutic applications of several decoy ODNs targeting transcription factors including NF-kB, [35][36][37] AP-1, 38-40 E2F, 54 Sp1, 55,56 and the signal transducer and activator of transcription (STAT) family. 57,58 There have also been a few reports suggesting an active role of AP-1 during the pathogenesis of IBD. Ishiguro et al 31 These observations suggest that control of AP-1 signaling may be a potent therapeutic target for treating IBD.…”
Section: Effects Of Decoy Odns On Expression Of Proinflammatory Cytokmentioning
confidence: 99%
“…20,21 To determine whether STAT6 plays a critical role in P-selectin expression, we prepared STAT6 decoy ODNs and treated HDMECs with the ODNs after incubation with substance P. In vitro treatment of HDMECs with STAT6 decoy ODNs reduced substance P-induced P-selectin expression (Figure 8). Similarly, IL-4-induced P-selectin expression was inhibited by STAT6 decoy ODNs.…”
Section: Transfection Of a Cis Element Decoy Against Stat6-binding Simentioning
confidence: 99%